Influence of radiofrequency surgery on architecture of the palatine tonsils - Plzak, Jan; Macokova, Pavla; Zabrodsky, Michal; Kastner, Jan; Lastuvka, Petr; Astl, Jaromir (BioMed research international, 2014)
Radiofrequency surgery is a widely used modern technique for submucosal volume reduction of the tonsils. So far there is very limited information on morphologic changes in the human tonsils after radiofrequency surgery. We performed histopathological study of tonsillectomy specimens after previous bipolar radiofrequency induced thermotherapy (RFITT). A total of 83 patients underwent bipolar RFITT for hypertrophy of palatine tonsils. Tonsil volume reduction was measured by 3D ultrasonography. Five patients subsequently underwent tonsillectomy. Profound histopathological examination was performed to determine the effect of RFITT on tonsillar architecture. All tonsillectomy specimens showed the intact epithelium, intact germinal centers, normal vascularization, and no evidence of increased fibrosis. No microscopic morphological changes in tonsillectomy specimens after bipolar RFITT were observed. RFITT is an effective submucosal volume reduction procedure for treatment of hypertrophic palatine tonsils with no destructive effect on microscopic tonsillar architecture and hence most probably no functional adverse effect.
Keywords: Palatine Tonsil; Tonsillectomy; indukovaná hypertermie; mladiství; Radiofrequency Therapy; mužské pohlaví; Adult; mladý dospělý; Hyperthermia, Induced; krční mandle; radiofrekvenční terapie; Organ Size; velikost orgánu; Young Adult; ženské pohlaví; Humans; dospělí; Female; Adolescent; tonzilektomie; lidé; Male